2006
DOI: 10.1002/ijc.21757
|View full text |Cite
|
Sign up to set email alerts
|

Tumor–stromal interactions reciprocally modulate gene expression patterns during carcinogenesis and metastasis

Abstract: This study used a unique xenogeneic breast cancer model to study the effects of tumor cells and neighboring host cells upon each other in tumor growth and metastasis. It exploited species differences between the interacting components to determine how the host influenced the tumor and vice versa. It was found that the gene expression profiles of highly and poorly metastatic clones from the same human breast carcinoma changed differentially when the cells were transferred from growth in vitro to the mammary gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 37 publications
3
47
0
Order By: Relevance
“…On the other hand, a series of data revealed differences in the expression signatures of tumors derived from cloned weakly/non-metastatic human cell lines and from their isogenic metastatic counterparts of the same patient [19,20]. This is in line with previous studies, which provided direct proof that individual malignant cells, co-existing within a given tumor, differ in metastatic capability [21].…”
Section: Discussionsupporting
confidence: 80%
“…On the other hand, a series of data revealed differences in the expression signatures of tumors derived from cloned weakly/non-metastatic human cell lines and from their isogenic metastatic counterparts of the same patient [19,20]. This is in line with previous studies, which provided direct proof that individual malignant cells, co-existing within a given tumor, differ in metastatic capability [21].…”
Section: Discussionsupporting
confidence: 80%
“…The results of this study demonstrated that dramatic gene expression changes occur in all cell types, including tumor epithelial, endothelial, and myoepithelial cells, myofibroblasts, fibroblasts, and leukocytes, during breast tumor progression. Similarly, gene expression [37] and enzyme activity [38] profiles of human breast cancer cell lines grown in three different ways: (1) in vitro cultures, (2) primary tumors in the mammary fat pad, and (3) distant metastases in different organs, showed changes in both epithelial cells and neighboring host stroma, suggesting reciprocal interactions during tumor formation and metastasis.…”
Section: Phenotypic and Molecular Alterations In The Tumor Microenvirmentioning
confidence: 99%
“…1,2 For breast cancer surgery and treatment, it is necessary to define the TME of a tissue, which is important in tumor progression. Nevertheless, no attempt has been made to define the TME of an actual tissue area.…”
mentioning
confidence: 99%